HUBUNGAN KEAKTIFAN BERORGANISASI DENGAN KETERAMPILAN BERBICARA SISWA KELAS XI SMK ISLAM INAYAH UJUNG BATU - Tifani Yusdar Triana; Silvia Permatasari; Oki Rasdana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the level of organizational activeness among grade XI students at SMKIslam Inayah Ujung Batu and its correlation with speaking skills. The research is quantitative with acorrelational approach. The population consists of all grade XI students at SMK Islam Inayah Ujung Batu, whilethe sample includes grade XI students from the Computer Network Engineering (TKJ), Electrical Power (LP),and Office Administration and Marketing (APHP) majors, selected using purposive sampling (non-probability).Data were collected using questionnaires, tests, documentation, and records. The independent variable X(organizational activeness) was measured via questionnaires, while the dependent variable Y (speaking skills)was measured through tests. Data analysis was assisted by IBM SPSS Statistics for Windows through thefollowing stages: (1) descriptive statistical analysis, (2) prerequisite tests including normality test, linearity test,correlation test, and significance test. The results show that students organizational activeness level is in the veryhigh category, while speaking skills are in the moderate/adequate category. The correlation coefficient 0.562falls into the moderate/adequate category. The significance value 0.001 0.05 indicates a significant influencebetween organizational activeness and speaking skills. The magnitude of this influence is reflected in thecoefficient of determination 0.316, meaning organizational activeness contributes 31.6% to students speakingskills in grade XI at SMK Islam Inayah Ujung Batu..Keywords: Organizational Activeness, Speaking Skills.